General hospital operational policy / Julina Md Noor ... [et al.] - Md Noor, Julina; Mohd Mokhtar, Mohd Amin; Kasim, Sazzli Shahlan; Mohamed Ali, Fatim Zulaika; Ruselan, Mahfuzah (UiTM Press, 2021)
Alhamdulillah, with His grace, I am pleased to introduce our very own General Hospital Operating Policy (GHOP), which illustrates the Hospital and the University's commitment to excellence in serving the Ummah. This document is a statement of intent. It serves as a roadmap for day-to-day operations of Hospital University Teknologi MARA (HUiTM). This document will provide us with the proper guidance, uniformity, accountability and efficiency during the deliverance of healthcare, catapulting us to the next level in patient safety and well-being, bringing forth a safer and more conducive workplace for the hospital staff. Through this document, we aim to guide doctors, nurses and healthcare workers in understanding their roles and responsibilities better. This document contains general policies related to the management and operations of the hospital. It also contains the policies on hospital and clinical governance, disaster management and contingency plans for the hospital. The stepping stones have been laid here. The future holds hope for those who strive for it. Aim higher and achieve goals you never expect. It is our aspiration that this policy will be the leading principles in bringing the Hospital and the University to greater heights.